Bi‐allelic variants in MDH2: Expanding the clinical phenotype. Issue 2 (22nd November 2021) - Ticci, Chiara; Nesti, Claudia; Rubegni, Anna; Doccini, Stefano; Baldacci, Jacopo; Dal Canto, Flavio; Ragni, Luca; Cordelli, Duccio M.; Donati, Maria Alice; Santorelli, Filippo M.
Abstract: Bi‐allelic alterations in the MDH2 gene have recently been reported in three unrelated toddlers with early‐onset severe encephalopathy. Here, we describe a new case of a child carrying novel variants in MDH2 . This child presented with early‐onset encephalocardiopathy requiring heart transplant and showed cerebellar ataxia and drug‐responsive epilepsy; his family history was significant for multiple cancers, a feature often associated with monoallelic variants in MDH2 . Functional studies in cultured skin fibroblasts from the proband showed reduced protein levels and impaired enzyme activity, further corroborating the genetic results. The relatively mild neurological presentation and severe cardiac manifestations requiring heart transplant distinguish this case from previous reports. This patient thus expands the spectrum of clinical features associated with MDH2 variants. Abstract :